PENERAPAN PROJECT BASED LEARNING PADA KURIKULUM MERDEKA DI SMK BIDANG TEKNOLOGI INFORMASI - Niti Wijaya, Agung Wahyu; Ahmad Dziqro Attayyu Setio Damar'; Arafina A’zzahra; Bunga Aulia Putri Maharani; Mohammad Wildan Habibi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The current development of the education system demands learning processes that not only emphasize theoretical understanding but also focus on developing skills that are relevant to workplace needs, particularly at the Vocational High School (SMK) level in the field of Information Technology. One of the learning models that supports this objective is Project Based Learning (PjBL), which encourages students to actively participate in learning activities through project completion. This study aims to analyze the implementation of Project Based Learning within the Merdeka Curriculum at SMK, especially in the Information Technology field. The research method applied in this study is a literature review by examining various relevant scientific articles and journals. Based on the analysis of approximately 30 articles, the findings indicate that the implementation of PjBL provides positive effects on students’ learning outcomes in cognitive, psychomotor, and affective domains. Improvements in learning outcomes can be seen from the increase in students’ average scores and learning completion percentages, with several studies reporting significant improvements of more than 80% and classical completion rates above 90%. In addition, PjBL has also been proven to enhance students’ practical abilities, creativity, critical thinking skills, and teamwork. In the psychomotor domain, the improvement in practical skills was found to be more dominant, while in the affective domain there were notable increases in students’ motivation, participation, and independent learning. Therefore, it can be concluded that the implementation of Project Based Learning (PjBL) contributes positively to supporting the implementation of the Merdeka Curriculum in Vocational High Schools, particularly in the field of Information Technology, by improving learning outcomes, student engagement, critical thinking, creativity, collaboration, and practical skills.